Analisis Peran Guru dalam Mengembangkan Karakter Kemandirian Anak Usia Dini di TK Suka Haji Kabupaten Bandung - Zihan Salsiah Nur; Dianti Yunia Sari; Agus Ruswandi (Journal of Early Education and Parenting, 2023)
This research is based on the importance of the teacher's role in developing the character of early childhood independence. So the purpose of this study is to find out the character of children's independence, to find out the role of the teacher during the learning process in developing the character of children's independence, to find out what are the supporting and inhibiting factors in developing the character of children's independence. This research uses a descriptive qualitative approach. Collection techniques through observation techniques interviews and documentation. The data sources of this research are group B teachers, group B3 students. Furthermore, in data analysis techniques, researchers use the Miles and Huberman model, namely data reduction, data presentation and drawing conclusions. The results showed that the independence of group B children was in accordance with their developmental stages, in physical abilities shown by the ability of children to wear their own shoes, responsible as evidenced by the child's ability when doing tasks from the teacher the child tries to complete it, sociable can be seen from the child's ability to socialize with classmates even though school has only been held for two weeks but children have been able to socialize and discipline, able to express opinions, control emotions reasonably. The role of the teacher in developing independence is as a model, guide, trainer, motivator and assessor and the supporting factors in developing children's independence are the role of educators, learning strategies, learning methods, and adequate facilities.